2016
DOI: 10.1002/ijc.29992
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin L inactivation leads to multimodal inhibition of prostate cancer cell dissemination in a preclinical bone metastasis model

Abstract: It is estimated that approximately 90% of patients with advanced prostate cancer develop bone metastases; an occurrence that results in a substantial reduction in the quality of life and a drastic worsening of prognosis. The development of novel therapeutic strategies that impair the metastatic process and associated skeletal adversities is therefore critical to improving prostate cancer patient survival. Recognition of the importance of Cathepsin L (CTSL) to metastatic dissemination of cancer cells has led to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…Similar to most weight loss trials, we also detected a solid correlation between the rate of weight loss and the loss of lean mass, although it is interesting to see that weight loss invokes similar catabolic gene expression profiles within the prostatic tumour, as observed in heart or skeletal muscle. Upregulation of CTSL is of concern because of its association with increased osteoclast formation, bone resorption, bone loss, and metastatic potential ( Sudhan et al , 2016 ). Given that the intervention was effective in reducing caloric intake, but not as effective in increasing PA, it is speculated that perhaps the losses in lean mass could have been mitigated and the upregulation of CTSL diminished if we had been able to activate men in the WLI arm, and include both aerobic and resistance PA.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to most weight loss trials, we also detected a solid correlation between the rate of weight loss and the loss of lean mass, although it is interesting to see that weight loss invokes similar catabolic gene expression profiles within the prostatic tumour, as observed in heart or skeletal muscle. Upregulation of CTSL is of concern because of its association with increased osteoclast formation, bone resorption, bone loss, and metastatic potential ( Sudhan et al , 2016 ). Given that the intervention was effective in reducing caloric intake, but not as effective in increasing PA, it is speculated that perhaps the losses in lean mass could have been mitigated and the upregulation of CTSL diminished if we had been able to activate men in the WLI arm, and include both aerobic and resistance PA.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, tumor progression studies in CTSL −/− mice revealed that CTSL deficiency significantly hampered the progression of benign encapsulated pancreatic tumors into highly invasive carcinomas [21]. Further, our previous findings have reported that pharmacological inhibition of CTSL using 3-bromophenyl-3-hydroxyphenyl-ketone thiosemicarbazone (KGP94) significantly impairs the invasive and metastatic capacities of human breast and prostate cancer cells [2224]. While these studies are clearly indicative of the importance of CTSL in metastatic progression, they shed little light on the involvement of CTSL in the angiogenic process.…”
Section: Introductionmentioning
confidence: 99%
“…CTSL, a lysosomal endopeptidase expressed in most eukaryotic cells, is a member of the papain-like family of cysteine proteinases, which is reported to be associated with cancer tumorigenesis, proliferation and migration [14]. CTSL has been proven to be upregulated in a variety of malignancies, and the level of CTSL expression is associated with the degree of malignancy [1516]. …”
Section: Discussionmentioning
confidence: 99%